2006
DOI: 10.1038/sj.bjc.6603395
|View full text |Cite
|
Sign up to set email alerts
|

Weekly cisplatin, epirubicin, and paclitaxel with granulocyte colony-stimulating factor support vs triweekly epirubicin and paclitaxel in locally advanced breast cancer: final analysis of a sicog phase III study

Abstract: The present study aimed at evaluating whether a weekly cisplatin, epirubicin, and paclitaxel (PET) regimen could increase the pathological complete response (pCR) rate in comparison with a tri-weekly epirubicin and paclitaxel administration in locally advanced breast cancer (LABC) patients. Patients with stage IIIB disease were randomised to receive either 12 weekly cycles of cisplatin 30 mg m À2, epirubicin 50 mg m À2, and paclitaxel 120 mg m À2 (PET) plus granulocyte-colony stimulating factor support, or fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…Variability in scan timing and timing relative to treatment may also have contributed to variable performance. In our cohort, only 18% of patients had a pCR, a result that is consistent with other trials in locally advanced breast cancer, using standard anthracycline–taxane combination chemotherapy in patients with heterogeneous tumor subtypes (3032). It is also important to realize the unbalanced number of patients between the pCR and no-pCR groups (9 vs. 42).…”
Section: Discussionsupporting
confidence: 91%
“…Variability in scan timing and timing relative to treatment may also have contributed to variable performance. In our cohort, only 18% of patients had a pCR, a result that is consistent with other trials in locally advanced breast cancer, using standard anthracycline–taxane combination chemotherapy in patients with heterogeneous tumor subtypes (3032). It is also important to realize the unbalanced number of patients between the pCR and no-pCR groups (9 vs. 42).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, clinical response following neoadjuvant chemotherapy did not well predict pathologic response. Of all patients, 22% achieved p cr , a result that is essentially consistent with other trials in labc (mostly using standard anthracycline–taxane combination chemotherapy) 1114. None of the patients in the present study with ibc achieved p cr , indicating the aggressive—and probably distinct—nature of this disease entity that begs for novel treatment strategies.…”
Section: Discussionsupporting
confidence: 89%
“…One trial [59] analysed the efficacy of different taxane doses of single-agent paclitaxel in the metastatic setting, and another [60,61] compared cisplatin, epirubicin, and paclitaxel to epirubicin and paclitaxel. Neither trial reported a test of interaction.…”
Section: Resultsmentioning
confidence: 99%